Standard language proficiency as social capital: Impacts on subjective socioeconomic status in China - Yangyang Wei; Xin Cai (PLoS ONE, 2025)
Although language proficiency—especially in a standard language—has been widely studied as an indicator of social status and mobility, its relationship with subjective socioeconomic status (SES) requires closer examination. Drawing on data from the 2021 China General Social Survey, this study investigates the relationship between Mandarin proficiency and Chinese individuals’ subjective SES, including subjective class identity and perceptions of social mobility. The sample comprises 5,997 individuals aged 18–95 from urban and rural areas nationwide, with balanced sex distribution and diverse educational and occupational backgrounds. Mandarin proficiency is positively associated with static subjective class identity. This association is more pronounced among younger, less-educated, and rural groups. Additionally, proficiency alleviates the downward deviation, where subjective class identity falls below objective SES. This effect is stronger in coastal regions. However, it shows little association to perceptions of past or future mobility. Karlson-Holm-Breen (KHB) decomposition reveals that job and life satisfaction partially mediate the relationship, with life satisfaction exerting a stronger influence. These findings underscore the role of Mandarin proficiency as social capital, reflecting individuals’ perceptions of their social position. The findings also provide empirical evidence to inform state-led language standardization policies that promote social integration and reduce disparities.